Choosing a New Organization for Management and Disposition of Commercial and Defense High-Level Radioactive Materials - Davis, Lynn E. (RAND Corporation, 2012)
Finding ways to safely store and ultimately dispose of nuclear waste remains a matter of considerable debate. This volume describes the steps needed to design a new, single-purpose organization to manage and dispose of commercial and defense high-level radioactive materials and examines three models for such an organization-federal government corporation, federally chartered private corporation, and independent government agency.